EVALUASI KEBIJAKAN PENYELENGGARAAN KEBERSIHAN DI KOTA BANJARMASIN - Muhammad Riduansyah Syafari (Universitas Sultan Ageng Tirtayasa, 2017)
Population growth in urban area, especially in a big town always appears the environment problems. One of the cases that often occured is the town garbage problem. In Banjarmasin Town, South Kalimantan Province, town garbage problem is the public issue that needed to be solved by local government, especially in 2007- 2007 period. This research aimed to explore policy implementation of town garbage management at Banjarmasin. To analyze this policy, author use performance concept for government institution, that contained of : policy input, policy output, policy effect and policy outcome. These aspect theoriyically will bring government’s effort into policy goals.This study used qualitative approach with using descritive analysis from data and information that gathered by observation and in-depth interview as primary data. Beside it, also used secondary data that contains of annual report, regulation and other written policy that related to garbage management and town-space policy of banjarmasin Municipality. The informan as source were the policy makers and policy implementor of garbage management and several stake-holders, especially itizen as the beneficiary of policy.Based on 2 yearly programmes, garbage management in Banjarmasin had done well that can be seen from its programme output and outcomes. Cleanliness environment in town also got well compared with its condition before. For these phenomenon, author recommend to carry out dissemination that advocation up to small groups in each sub district and supervizing on-going garbage management policy implementation.